Assessing the Impact of E-Commerce, Accounting Information Systems, and Business Capital on Students’ Entrepreneurial Interest - Mahadewi, Ade Gita; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 34 No 9 (2024), 2024)
As we approach the end of this decade, an increasing number of students are venturing into entrepreneurship, driven by the accessibility of information and advancements in technology. This study seeks to provide empirical evidence on the impact of E-Commerce, Accounting Information Systems, and Business Capital on the entrepreneurial interests of students. The research focuses specifically on accounting students at Udayana University, with a sample size of 41 participants selected through a saturated sampling method. Data were collected via a structured questionnaire, and the analysis was conducted using multiple linear regression techniques. The results of the study indicate that E-Commerce, Accounting Information Systems, and Business Capital significantly and positively influence students' interest in pursuing entrepreneurship. Keywords: E-Commerce, Accounting Information Systems, Business Capital, Student Interest in Entrepreneurship.